IMPACT EVALUATION OF THE SCHOOL OPERATIONAL ASSISTANCE PROGRAM (BOS) USING THE MATCHING METHOD - Eny Sulistyaningrum (Journal of Indonesian Economy and Business (JIEB), 2016)
Investment in human capital, especially in children’s education, is considered to be among the most effective ways for countries to improve their national welfare and reduce poverty in the long term. The Government of Indonesia has promoted human capital investment, especially in children, by designing school subsidy programs. Since 2005, the school operational assistance program (BOS) has been the biggest school subsidy program in Indonesia during the last two decades. This paper evaluates the impact of BOS on children’s test scores at the early stage. This study uses Propensity Score Matching (PSM) to estimate the average treatment effect, in the absence of selection, on unobserved characteristics. The results confirm that BOS can increase student performance. The finding suggests that the Government of Indonesia needs to develop a subsidy program to provide a basic level of education for all students, especially for the poor, as the recent school subsidy program is only sufficient for school fees or even only enough for tuition fees if the students live in urban areas. The remainder of the education expenditures must be covered by the household.Keywords: School Subsidy, BOS, PSM, Test ScoresJEL: H52, I22, I25